Three-dimensional inkjet-printed redox cycling sensor. Issue 9 (17th January 2017) - Adly, N. Y.; Bachmann, B.; Krause, K. J.; Offenhäusser, A.; Wolfrum, B.; Yakushenko, A.
Abstract : Electrochemical amplification through redox cycling in an all-inkjet-printed device utilizing four different functional inks. Abstract : Multilayer inkjet printing is emerging as a robust platform for fabricating flexible electronic devices over a large area. Here, we report a straightforward, scalable and inexpensive method for printing multilayer three-dimensional nanoporous redox cycling devices with a tunable nanometer gap for electrochemical sensing. The fabrication of the electrochemical redox cycling device is based on vertical stacking of two conductive electrodes made of carbon and gold nanoparticle inks. In this configuration, the two electrodes are parallel to each other and electrically separated by a layer of polystyrene nanospheres. As the top and the bottom electrodes are biased to, respectively, oxidizing and reducing potentials, repetitive cycling of redox molecules between them generates a large current amplification. We show that a vertical interelectrode spacing down to several hundred nanometers with high precision using inkjet printing is possible. The printed sensors demonstrate excellent performance in electrochemical sensing of ferrocene dimethanol as a redox-active probe. A collection efficiency of 100% and current amplification up to 30-fold could be obtained. Our method provides a low cost and versatile means for sensitive electrochemical measurements eliminating the need for sophisticated fabrication methods, which could prove useful for sensitive point-of-care diagnostics devices.